Scaling-up urban agriculture for a healthy, sustainable and resilient food system: the postharvest benefits, challenges and key research gaps - Kourmpetli, Sofia; Falagán, Natalia; Hardman, Charlotte; Liu, Lingxuan; Mead, Bethan; Walsh, Lael; Davies, Jess (Inderscience, 2022)
Sustainably ensuring food security and safety for the urban population is a major challenge. In this perspective, we present the concept of rurbanisation (the ruralisation of urban areas through increased urban agriculture) as a holistic strategy to provide a resilient food system. In particular, we focus on the postharvest benefits of urban agriculture for environmentally sustainable food supply chains, enhanced nutritional content of fresh produce and access to fresh, local and seasonal food. However, upscaling current urban agricultural systems requires improvement in current technologies and local infrastructure as well as the transfer of knowledge and skills to new urban farmers. This perspective summarises the main challenges that urban agriculture is currently facing from a postharvest quality and safety point of view, and highlights the research gaps and opportunities for improvements in that area.
Keywords: Urban agriculture; health; Sustainability; food system; resilience; postharvest benefits; rurbanisation